2011
DOI: 10.4103/0974-620x.83657
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction regarding eye care services at tertiary hospital of central India

Abstract: Purpose:To evaluate patients’ satisfaction regarding eye care services and suggest policy changes accordingly.Study Design:Descriptive study.Materials and Methods:This study was conducted between September 2005 and June 2006. Patients attending the eye clinic of Sadguru Netra Chikitsalaya, Chitrakoot, Madhya Pradesh, India, and admitted as in-patients in this hospital were our study population. Randomly selected patients were interviewed by trained staff. Close-ended questionnaire was used to conduct these str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
2
8
1
1
Order By: Relevance
“…The demographics of respondents in this study is not significantly different from other studies on patient satisfaction of health care services even though they were not specifically done for ophthalmic counselling services. 9 , 11 , 14 , 18 The high level of patients' satisfaction with time spent (75%) and overall services received (76.7%) indicates that the ophthalmic counselling services met the respondents' needs and expectations. Taking into consideration the very satisfied group, this study shows that over 80% and about 90% were satisfied with time spent and overall counselling service received respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The demographics of respondents in this study is not significantly different from other studies on patient satisfaction of health care services even though they were not specifically done for ophthalmic counselling services. 9 , 11 , 14 , 18 The high level of patients' satisfaction with time spent (75%) and overall services received (76.7%) indicates that the ophthalmic counselling services met the respondents' needs and expectations. Taking into consideration the very satisfied group, this study shows that over 80% and about 90% were satisfied with time spent and overall counselling service received respectively.…”
Section: Discussionmentioning
confidence: 99%
“… 28 While all these studies reported low patient satisfaction with WASH provision, a study in an eye care hospital in India reported high patient satisfaction with toilets (83.2%), water facilities (99.4%) and cleanliness (99.4%). 29 Indeed, no respondent judged these as poor. However, 16.9% did not answer the toilet question.…”
Section: Resultsmentioning
confidence: 99%
“…(8) All respondents declared high degree of satisfaction for accessibility of the OPD and its location (82.9%) which was consistent with the findings by Mohd to information received and courteousness of staff at the registration counter, the study participants had shown high satisfaction level which was same as that of the study where participants had expressed high satisfaction with the attitude and behaviour of health staff, explanation and guidance given to them. (11,12) All respondents expressed a good satisfaction judgement against certain structural attributes like seating facility and toilet facilities. Also, there existed a high level of satisfaction of all respondents in respect to availability of drinking water at the registration.…”
Section: Discussionmentioning
confidence: 97%